Cover Image. Issue 5 (26th April 2018) - Mosińska, P.; Jacenik, D.; Sałaga, M.; Wasilewski, A.; Cygankiewicz, A.; Sibaev, A.; Mokrowiecka, A.; Małecka‐Panas, E.; Pintelon, I.; Storr, M.; Timmermans, J. P.; Krajewska, W. M.; et al.
Abstract : The cover image, by P. Mosińska et al., is based on the Original Article FABP4 blocker attenuates colonic hypomotility and modulates white adipose tissue‐derived hormone levels in mouse models mimicking constipation‐predominant IBS, DOI:10.1111/nmo.13272 .